2022
DOI: 10.1210/clinem/dgac181
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster Randomized Noninferiority Field Trial of Gestational Diabetes Mellitus Screening

Abstract: Context Although it is well-acknowledged that gestational diabetes mellitus (GDM) is associated with the increased risks of adverse pregnancy outcomes, the optimal strategy for screening and diagnosis of GDM are still a matter of debate. Objective This study was conducted to demonstrate the non-inferiority of less strict GDM-screening criteria compared to the strict International Association of the Diabetes and Pregnancy Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…One of the important strengths of our study is the generalizability of findings due to its characteristics, including its design as a community-based trial, large sample size, the geographic distribution of the regions involved, and using similar laboratory protocols. In addition, the adherence to each protocol in our study was high ( 25 ), which could increase the validity of our findings.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…One of the important strengths of our study is the generalizability of findings due to its characteristics, including its design as a community-based trial, large sample size, the geographic distribution of the regions involved, and using similar laboratory protocols. In addition, the adherence to each protocol in our study was high ( 25 ), which could increase the validity of our findings.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, the Iranian Ministry of Health and Medical Education (MoHME) approved the study protocol, and pre-specified GDM modalities were made available to all those provinces as mandatory guidelines. Detailed methods have been described elsewhere ( 24 , 25 ). Briefly, a total of 35,613 pregnant women in the first trimester of pregnancy from five different geographic regions of Iran were recruited.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a secondary analysis of a randomized community non-inferiority trial among pregnant women in the GULF Study. Detailed methods and results of the main trial have been reported previously 23 24. Briefly, this study was conducted to determine non-inferiority of less strict GDM screening criteria compared with the stringent IADPSG criteria with respect to maternal and neonatal outcomes, in which 35 430 pregnant women in the first trimester of pregnancy, aged 18 years and over from five different geographic regions of Iran participated.…”
Section: Methodsmentioning
confidence: 99%